High-barrier biodegradable food packaging film and preparation method thereof

By modifying materials such as graphene and chitosan-sodium alginate composites, combining nano-interlayer structure and intelligent responsive materials, the high barrier, wear resistance, ductility and environmental monitoring of food packaging films are solved, and the problem of high barrier, wear resistance, ductility and environmental monitoring of food packaging films is achieved. Long-term preservation and environmental protection goals of food.

CN119144165APending Publication Date: 2024-12-17HANGSHI TECH DEV (HANGZHOU) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411411411.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing food packaging films are difficult to achieve high barrier, high wear resistance, high ductility of packaging film raw materials, multi-layer composite multi-function of packaging films, and the function of monitoring the internal environment of the packaging, resulting in accelerated deterioration of foods under unsuitable conditions, and shelf life Shorten, consume a large amount of non-renewable resources, generate a large amount of waste, pollute the environment, and affect food safety and quality.

Method used

High barrier biodegradable food packaging film consisting of modified graphene, chitosan-sodium alginate complex, nanolayer structure, enzymatic degradation enhancer, intelligent responsive materials and new starch derivatives, etc., through modification The graphene achieves high barrier and high wear resistance, the chitosan-sodium alginate complex improves ductility, the nano-interlayer structure realizes multi-layer composite function, and the packaging internal environment is monitored through leakage indicators.

Benefits of technology

It realizes high barrier and wear resistance, extends the shelf life of food, reduces waste generation, improves packaging flexibility and food freshness, improves food safety and market competitiveness, and promotes environmental protection and sustainable development. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144165A_ABST
    Figure CN119144165A_ABST
Patent Text Reader

Abstract

The invention discloses a high-barrier-property biodegradable food packaging film and a preparation method thereof, and relates to the technical field of food packaging. Comprising the following main components in parts by weight: 4-25 parts of a polymeric hybrid, 6-15 parts of an enzymatic degradation enhancer, 10-25 parts of a barrier material, 55-80 parts of a bio-based polymer, 30-40 parts of an intelligent degradation regulator, an intelligent responsive material, 10-15 parts of a novel starch derivative, 13-27 parts of novel polyester bio-ester and 20-40 parts of a chitosan-sodium alginate compound. Through the modified graphene, the high-barrier and high-wear-resistant biodegradation function is realized, the problems of food oxidation, dampness and deterioration caused by gases such as oxygen, water vapor and carbon dioxide are solved, and the shortening of the shelf life of food and the accumulation of wastes are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of food packaging, in particular to a high-barrier biodegradable food packaging film and a preparation method thereof. Background Art

[0002] Food packaging film is an important material for protecting food, extending shelf life and improving product appearance.

[0003] With the rapid development of the food industry and consumers' increasing requirements for food quality, the demand for food packaging films is growing. Especially in the context of globalization and the rise of e-commerce, long-distance transportation and long-term storage of food have put forward higher requirements on the performance of packaging films.

[0004] In order to meet market demand and environmental protection requirements, the food packaging film industry continues to make technological innovations, such as developing new packaging materials such as degradable, edible, and high barrier properties, and improving the preparation process of packaging films to improve production efficiency and product quality.

[0005] Therefore, it is very necessary to propose a high-barrier biodegradable food packaging film and a preparation method thereof in the present application to solve the problems in the background.

[0006] Patent document CN114437516B discloses a high-barrier, high-transmittance biodegradable film and a preparation method thereof. The above patent realizes that compared with traditional films and pure PBAT films, the high-barrier, high-transmittance, fully biodegradable film prepared by the present invention has obvious application advantages in the fields of fruit and vegetable food packaging, mulch films, etc. The film is composed of aliphatic polycarbonate (5-30%), polybutylene adipate / terephthalate PBAT (65-90%), chain extender and compatibilizer (0.5-3%), modified amorphous silica (0.1-3%), antioxidant (0.1-1%), composite ultraviolet absorber (0.5-2%), etc.; the film preparation method is to extrude through a twin-screw extruder and granulate through a pelletizer to obtain a uniform mixed pellet, and then blow the mixed pellet to obtain a high-barrier, high-transmittance biodegradable film, but the above patent cannot achieve high-barrier, high-wear-resistant and biodegradable functions.

[0007] Patent document CN113234307B discloses a fully degradable antibacterial food packaging film and a preparation method thereof. The above patent realizes that the produced fully degradable antibacterial food packaging film has excellent antibacterial properties, mechanical properties and barrier properties, the antibacterial agent used is highly safe, and the film making method adopted is continuous and efficient. The fully degradable antibacterial food packaging film is suitable for commercial production and can be used in a variety of food packaging scenarios, but the above patent cannot realize the function of strong ductility of the raw materials of the packaging film.

[0008] Patent document CN113354853B discloses a biodegradable high barrier antibacterial composite film and its preparation method. The above patent realizes the preparation of a biodegradable high barrier antibacterial composite film by casting or scraping film by using nanocellulose composite polylactic acid as the base material, adding barrier substances, antibacterial substances and plasticizers. The preparation method of the present invention is simple and effective. The prepared biodegradable high barrier antibacterial composite film has good barrier properties and mechanical properties, significant antibacterial properties, and is biodegradable, but the above patent cannot achieve multi-layer composite multifunctional packaging film.

[0009] Patent document CN114536921B discloses a method for preparing an antioxidant food packaging film. The above patent achieves that the prepared packaging film has good barrier properties and low permeability, with an oxygen permeability of 0.03-0.04cm3 / (m2·24h·0.1Mpa) and a carbon dioxide permeability of 0.05-0.06cm3 / (m2·24h·0.1Mpa). The packaging film prepared by the present invention has a low water vapor permeability of 0.35-0.38g / (m2·24h), but the above patent cannot achieve the function of monitoring the internal environment of the package.

[0010] In summary, the above patents cannot achieve the functions of high barrier and high wear resistance and biodegradability, strong ductility of the raw materials of the packaging film, multi-layer composite and multi-functional packaging film, and monitoring the internal environment of the packaging, which results in the storage of food under unsuitable conditions, accelerates the deterioration process, shortens the shelf life, consumes a large amount of non-renewable resources such as petroleum, generates a large amount of waste accumulation, causes long-term pollution to the environment, is prone to wear and tear during transportation and storage, and causes food leakage and contamination, affecting the safety and quality of food, thereby reducing consumer trust and causing irreparable economic losses; To this end, the present application proposes a high-barrier biodegradable food packaging film and its preparation method which can realize high-barrier and high-wear-resistant biodegradable functions, strong ductility of the packaging film raw materials, multi-layer composite multi-functions of the packaging film and the function of monitoring the internal environment of the packaging. Summary of the invention

[0011] The object of the present invention is to provide a high-barrier biodegradable food packaging film and a preparation method thereof, so as to solve the technical problems proposed in the above-mentioned background technology that the high-barrier and high-wear-resistant biodegradable functions, the strong ductility of the packaging film raw materials, the multi-layer composite multi-functions of the packaging film and the function of monitoring the internal environment of the packaging cannot be achieved, resulting in the storage of food under inappropriate conditions, accelerating the deterioration process, shortening the shelf life, consuming a large amount of non-renewable resources such as petroleum, generating a large amount of waste accumulation, causing long-term pollution to the environment, and being easily worn and broken during transportation and storage, causing food leakage and pollution, and affecting the safety and quality of food.

[0012] To achieve the above-mentioned object, the present invention provides the following technical solutions: a high barrier biodegradable food packaging film, comprising the following main components and weight parts: 4-25 parts of polymer hybrid, 6-15 parts of enzymatic degradation enhancer, 10-25 parts of barrier material, 55-80 parts of bio-based polymer, 30-40 parts of intelligent degradation regulator, intelligent responsive material, 10-15 parts of novel starch derivative, 13-27 parts of novel polybioester, 20-40 parts of chitosan-sodium alginate complex; The polymer hybrid is modified graphene, the enzymatic degradation enhancer is cellulase, amylase, metal ions and coenzymes, the barrier material is polyvinyl alcohol ester, polyvinyl alcohol ether, polycaprolactone, microalgae film and polymer nanofiber, and the bio-based polymer is plant fiber and polyhydroxybutyrate; The food packaging film has a nano-interlayer structure.

[0013] Preferably, the smart responsive material is 0.5-2 parts of self-assembled microcapsules, the responsive monomer is N-isopropylacrylamide, the microcapsule shell is polylactic acid-polyethylene glycol copolymer, and the crosslinking agent is mercaptopropionic acid; The humidity-responsive polymer is polyvinyl alcohol, the photosensitive polymer is styrene, and the photocrosslinking agent is dinitrophenol; The acid-base responsive polymer is a polyacrylic acid compound, and the polyacrylic acid compound is sodium polyacrylic acid and acrylic acid-hydroxyethyl methacrylate copolymer.

[0014] Preferably, the intelligent degradation regulator includes a slow degradation agent and an acid-base regulator; The slow degradation agent uses polylactic acid enzyme and photosensitizer, and the photosensitizer uses benzophenone compounds, transition metal compounds and new degradable near-infrared photosensitizer; The benzophenone compounds have a ketone group in their molecular structure and can be easily excited by light. The benzophenone compounds are selected from acetophenone, hexachloroacetone, tetramethyl-4,4-diaminoketone, tetrabutyl thiophenone disulfide, and diphenylamine. The transition metal compound is selected from transition metal salts of N,N-dialkyldithiocarbamic acid, transition metal salts of salicylic acid, anatase titanium dioxide, calcium oxide, nickel dialkyldithiocarbamate and zinc, Zn, Mn, Ni, Co metal ion complexes, cerium carboxylate, cerium laurate and cerium stearate; The acid-base regulator uses 0.1-0.7 parts of citric acid, 0.2-0.4 parts of nano magnesium hydroxide and 0.1-0.3 parts of trisodium phosphate.

[0015] Preferably, the novel degradable near-infrared photosensitizer is a porphyrin compound and its derivatives, which degrade while generating active oxygen under illumination. When the illumination ends, the photosensitizer is completely converted into a low-toxic substance without photoactivity.

[0016] Preferably, the food packaging film further comprises the following components and parts by weight: 0.5-2 parts of toughening agent, 1-3 parts of nanofiber reinforcing agent, 0.3-0.6 parts of moisture control agent, antibacterial agent, 2-7 parts of polymer sealant, 0.6-1.8 parts of coating modifier, 0.5-0.9 parts of enzymolysis agent, 1-5 parts of microbial degradation agent, 1-9 parts of matting agent; The toughening agent is a bio-based toughening agent, which is a mixture of starch polymer and succinic acid; The humidity control agent adopts modified silica gel and bamboo charcoal; The antimicrobial agent used was 0.3 parts of glucomannan, 9 parts of aloe-emodin, and 15 parts of mannose-6-phosphate; The polymer sealant uses polyurethane; The coating modifiers are water-based polyurethane and water-based acrylic; The microbial degradation agent uses a composite microbial agent, Pseudomonas, Candida and Rhodotorula; The matting agent is a polyacrylate resin with an epoxy group, with a softening point between 120-130°C and a viscosity between 400-600cps.

[0017] Preferably, the polyhydroxybutyrate has a melting point of 175° C. and is produced by a microbial fermentation agent.

[0018] Preferably, the polycaprolactone is prepared by ring-opening polymerization of ε-caprolactone in the presence of a metal organic compound tetraphenyltin as a catalyst and dihydroxy / trihydroxy as an initiator, with a melting point of 60-63° C. and a density of 1.021 g / cm³.

[0019] Preferably, the starch polymer and succinic acid mixture is formed by combining starch polymer and succinic acid / succinic acid derivatives through an esterification reaction, with the starch polymer as the main chain and the succinic acid / succinic acid derivatives as the side chains, which are connected together through ester bonds.

[0020] Preferably, the preparation method comprises the following steps: (1) Weigh 20 g of chitosan and add it to 500 mL of 1% acetic acid solution. Use a magnetic stirrer to stir at room temperature (25°C) for 4 hours until the chitosan is completely dissolved to form a uniform transparent solution. Use NaOH solution to adjust the pH value of the chitosan solution to 5.5-6.0; (2) Weigh 20 g of sodium alginate and add it to 400 mL of deionized water. Stir at room temperature for 1 hour until it is completely dissolved to form a uniform viscous solution. (3) mixing the chitosan solution, the sodium alginate solution and the polymer hybrid suspension in a volume ratio of 1:1:0.5; (4) Add 30 mL of plasticizer, 20 g of barrier material, 1 g of antimicrobial agent, 2 g of intelligent degradation regulator, 0.5 g of photosensitizer, 0.2 g of methylene blue, 10 ml of anthocyanin and 0.2 g of bromocresol green and continue stirring at room temperature for 2 hours to ensure that all ingredients are evenly dispersed; (5) Place the mixed solution in a vacuum desiccator and treat it under negative pressure for 30 minutes to remove bubbles in the solution; (6) Slowly pour the degassed solution into the film applicator, apply the solution on a clean, flat film forming mold (Teflon plate) at a constant speed, and adjust the film applicator to control the film thickness (0.1-0.5 mm); (7) The coated film was placed at room temperature for 2 hours to allow the solvent to partially evaporate. The film was then transferred to a drying oven and dried at 50°C and 50% relative humidity for 12 hours. After drying, the film was taken out and equilibrated at room temperature and 65% relative humidity for 24 hours. The film was peeled off from the mold and then immersed in a 2 mmol / L polyvinyl alcohol ester solution for 30 minutes. After treatment, the film was repeatedly washed with deionized water to remove the unreacted polyvinyl alcohol ester solution. The treated film was dried in a drying oven at 40°C for 6 hours.

[0021] Preferably, the preparation method further comprises the following steps: (8) Preparation of polyhydroxybutylate Select Pseudomonas acidophilus / recombinant Escherichia coli, prepare fermentation medium, inoculate and ferment at about 37°C for 48-72 hours, collect bacteria and break cell walls, extract products with organic solvent chloroform, precipitate, filter and dry to obtain pure polyhydroxybutyrate; (9) Starch polymer and succinic acid mixture Disperse starch in water, adjust the pH to 8-9, slowly add octenyl succinic anhydride, control the temperature at 25-40°C, and react for 2-4 hours to graft the octenyl succinic acid groups onto the starch molecules; Add aluminum hydroxide solution to the esterified starch, stir evenly, and react for 0.5-2 hours to allow aluminum ions to combine with the esterified starch; The pH of the reaction solution is adjusted to 6-7 with hydrochloric acid / sodium hydroxide, the product is separated by centrifugation, and washed with water to remove unreacted raw materials and by-products; The wet product is dried at 50-60°C to constant weight, and the dried product is crushed and sieved to obtain fine powdered aluminum starch octenylsuccinate.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention achieves high barrier and high wear resistance biodegradation function by modifying graphene, solves the problem of food oxidation, moisture and deterioration caused by gases such as oxygen, water vapor and carbon dioxide, and avoids shortening of food shelf life and waste accumulation; 2. The present invention realizes the function of strong ductility of the raw material of the packaging film through the chitosan-sodium alginate complex, solves the problem of not being able to be tightly sealed during the packaging process, is easier to open and reseal, saves the production cost of the packaging film, and reduces the food safety risks caused by damage caused by various external forces and extrusion during food transportation, storage and sales; 3. The present invention realizes multi-layer composite and multifunctional packaging film through nano-interlayer structure, solves the problems of food fading or deterioration due to light, moisture caused by water, and easy damage to packaging, improves the freshness and taste of food, personalizes packaging, customizes product information, and enhances the brand image and market competitiveness of products; 4. The present invention realizes the function of monitoring the internal environment of the package through the leakage indicator, solves the problem of food being stored under unsuitable conditions and accelerating the deterioration process, reduces unnecessary waste, and promotes intelligent management and environmental protection and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the preparation process of the high barrier biodegradable food packaging film of the present invention; Figure 2 This is a schematic diagram of the process for preparing polyhydroxybutyrate of the present invention; Figure 3 The figure is a schematic diagram of the process of preparing a mixture of starch polymer and succinic acid according to the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0025] See also Figure 2 and Figure 3, a high barrier biodegradable food packaging film, comprising the following main components and weight parts: 4-25 parts of polymer hybrid, 6-15 parts of enzymatic degradation enhancer, 10-25 parts of barrier material, 55-80 parts of bio-based polymer, 30-40 parts of intelligent degradation regulator, intelligent responsive material, 10-15 parts of new starch derivatives, 13-27 parts of new polybioester, 20-40 parts of chitosan-sodium alginate complex, the enzymatic degradation enhancer uses cellulase, amylase, metal ions and coenzymes, the barrier material uses polyvinyl alcohol ester, polyvinyl alcohol ether, polycaprolactone, microalgae film and polymer nanofiber, the bio-based polymer uses plant fiber and polyhydroxybutyrate; the food packaging film has a nano-interlayer structure, the starch polymer and succinic acid mixture are formed by combining starch polymer and succinic acid / succinic acid derivatives through esterification reaction, the starch polymer is used as the main chain, and the succinic acid / succinic acid derivatives are used as the side chain, which are connected together through ester bonds; Further, polyhydroxybutyrate is prepared by selecting Pseudomonas acidophilus / recombinant Escherichia coli, preparing a fermentation medium, inoculating and fermenting at about 37°C for 48-72 hours, collecting the cells and breaking the cell walls, extracting the product with an organic solvent chloroform, precipitating, filtering, and drying to obtain pure polyhydroxybutyrate; Preparation of a starch polymer and succinic acid mixture: Disperse starch in water, adjust the pH to 8-9, slowly drop octenyl succinic anhydride, control the temperature at 25-40°C, react for 2-4 hours, and graft the octenyl succinic acid groups onto the starch molecules; Add aluminum hydroxide solution to the esterified starch, stir evenly, and react for 0.5-2 hours to allow aluminum ions to combine with the esterified starch; The pH of the reaction solution is adjusted to 6-7 with hydrochloric acid / sodium hydroxide, the product is separated by centrifugation, and washed with water to remove unreacted raw materials and by-products; The wet product is dried at 50-60°C to constant weight, and the dried product is crushed and sieved to obtain fine powdered aluminum starch octenylsuccinate. Example

[0026] See also Figure 1 , a high barrier biodegradable food packaging film, the intelligent responsive material is 0.5-2 parts of self-assembled microcapsules, the responsive monomer is N-isopropylacrylamide, the microcapsule shell is polylactic acid-polyethylene glycol copolymer, the crosslinking agent is mercaptopropionic acid, the humidity responsive polymer is polyvinyl alcohol, the photosensitive polymer is styrene, the photocrosslinking agent is dinitrophenol, the acid-base responsive polymer is a polyacrylic acid compound, and the polyacrylic acid compound is sodium polyacrylic acid and acrylic acid-hydroxyethyl methacrylate copolymer; Take the following raw material components and weight parts: 20g chitosan, 20g sodium alginate, 10g modified graphene, 30mL plasticizer, 20g barrier material, 1g antibacterial agent, 2g smart degradation regulator, 5g slow degradation agent, 6g polyvinyl alcohol ester, 0.5g photosensitizer, 0.2g methylene blue, 10ml anthocyanin and 0.2g bromocresol green; Further, (1) 20 g of chitosan was weighed and added to 500 mL of 1% acetic acid solution, and stirred at room temperature (25°C) for 4 hours using a magnetic stirrer until the chitosan was completely dissolved to form a uniform transparent solution, and the pH value of the chitosan solution was adjusted to 5.5 using a NaOH solution; (2) Weigh 20 g of sodium alginate, add it to 400 mL of deionized water, and stir it at room temperature for 1 hour until it is completely dissolved to form a uniform viscous solution. Weigh 10 g of modified graphene, add it to 250 mL of deionized water, and use an ultrasonic disperser to ultrasonicate for 30 minutes to obtain a stable polymer hybrid suspension; (3) mixing the chitosan solution, the sodium alginate solution and the polymer hybrid suspension in a volume ratio of 1:1:0.5; (4) Add 30 mL of plasticizer, 20 g of barrier material, 1 g of antimicrobial agent, 2 g of intelligent degradation regulator, 5 g of slow degradation agent, 0.5 g of photosensitizer, 0.2 g of methylene blue, 10 ml of anthocyanin and 0.2 g of bromocresol green and continue stirring at room temperature for 2 hours to ensure that all ingredients are evenly dispersed; (5) Place the mixed solution in a vacuum desiccator and treat it under negative pressure for 30 minutes to remove bubbles in the solution; (6) Slowly pour the degassed solution into the applicator, apply the solution on a clean, flat Teflon plate at a constant speed, and adjust the applicator to control the film thickness to 0.25 mm; (7) The coated film was placed at room temperature for 2 hours to allow the solvent to partially evaporate. The film was then transferred to a drying oven and dried at 50°C and 50% relative humidity for 12 hours. After drying, the film was taken out and equilibrated at room temperature and 65% relative humidity for 24 hours. The film was peeled off from the mold and then immersed in a 2 mmol / L polyvinyl alcohol ester solution for 30 minutes. After treatment, the film was repeatedly washed with deionized water to remove the unreacted polyvinyl alcohol ester solution. The treated film was dried in a drying oven at 40°C for 6 hours. Example

[0027] See also Figure 1, a high barrier biodegradable food packaging film, further comprising 0.5-2 parts of a toughening agent, 1-3 parts of a nanofiber reinforcement, 0.3-0.6 parts of a moisture control agent, an antibacterial agent, 2-7 parts of a polymer sealant, 0.6-1.8 parts of a coating modifier, 0.5-0.9 parts of an enzymolysis agent, 1-5 parts of a microbial degradation agent, and 1-9 parts of a matting agent; the toughening agent adopts a bio-based toughening agent, and the bio-based toughening agent is a mixture of starch polymer and succinic acid; The humidity control agent adopts modified silica gel and bamboo charcoal; The antimicrobial agent used was 0.3 parts of glucomannan, 9 parts of aloe-emodin, and 15 parts of mannose-6-phosphate; The polymer sealant uses polyurethane; The coating modifiers are water-based polyurethane and water-based acrylic; The microbial degradation agent uses a composite microbial agent, Pseudomonas, Candida and Rhodotorula; The matting agent is polyacrylate resin with epoxy group, with softening point between 120-130℃ and viscosity between 400-600cps. Take the following raw material components and weight parts: 20g chitosan, 20g sodium alginate, 5g modified graphene, 30mL plasticizer, 5g barrier material, 1g antibacterial agent, 2g smart degradation regulator, 5g slow degradation agent, 6g polyvinyl alcohol ester, 0.5g photosensitizer, 0.2g methylene blue, 10ml anthocyanin and 0.2g bromocresol green; Further, (1) 20 g of chitosan was weighed and added to 500 mL of 1% acetic acid solution, and stirred at room temperature (25°C) for 4 hours using a magnetic stirrer until the chitosan was completely dissolved to form a uniform transparent solution, and the pH value of the chitosan solution was adjusted to 5.5 using a NaOH solution; (2) Weigh 20 g of sodium alginate, add it to 400 mL of deionized water, and stir it at room temperature for 1 hour until it is completely dissolved to form a uniform viscous solution. Weigh 5 g of modified graphene, add it to 250 mL of deionized water, and use an ultrasonic disperser to ultrasonicate for 30 minutes to obtain a stable polymer hybrid suspension; (3) mixing the chitosan solution, the sodium alginate solution and the polymer hybrid suspension in a volume ratio of 1:1:0.5; (4) Add 30 mL of plasticizer, 20 g of barrier material, 1 g of antimicrobial agent, 2 g of intelligent degradation regulator, 5 g of slow degradation agent, 0.5 g of photosensitizer, 0.2 g of methylene blue, 10 ml of anthocyanin and 0.2 g of bromocresol green and continue stirring at room temperature for 2 hours to ensure that all ingredients are evenly dispersed; (5) Place the mixed solution in a vacuum desiccator and treat it under negative pressure for 30 minutes to remove bubbles in the solution; (6) Slowly pour the degassed solution into the applicator, apply the solution on a clean, flat Teflon plate at a constant speed, and adjust the applicator to control the film thickness to 0.25 mm; (7) The coated film was placed at room temperature for 2 hours to allow the solvent to partially evaporate. The film was then transferred to a drying oven and dried at 50°C and 50% relative humidity for 12 hours. After drying, the film was taken out and equilibrated at room temperature and 65% relative humidity for 24 hours. The film was peeled off from the mold and then immersed in 1 mmol / L polyvinyl alcohol ester solution for 30 minutes. After treatment, the film was repeatedly washed with deionized water to remove the unreacted polyvinyl alcohol ester solution. The treated film was dried in a drying oven at 40°C for 6 hours. Example

[0028] See also Figure 1 , a high barrier biodegradable food packaging film, polyhydroxybutylate has a melting point of 175°C, polyhydroxybutylate is made from microbial fermentation agents, polycaprolactone is produced by ring-opening polymerization of ε-caprolactone in the presence of metal organic compound tetraphenyltin as a catalyst and dihydroxy / trihydroxy as an initiator, with a melting point of 60-63°C and a density of 1.021g / cm³; Take the following raw material components and weight parts: 10g chitosan, 10g sodium alginate, 10g modified graphene, 30mL plasticizer, 20g barrier material, 1g antibacterial agent, 2g smart degradation regulator, 5g slow degradation agent, 6g polyvinyl alcohol ester, 0.5g photosensitizer, 0.2g methylene blue, 10ml anthocyanin and 0.2g bromocresol green; Further, (1) 10 g of chitosan was weighed and added to 500 mL of 1% acetic acid solution, and stirred at room temperature (25°C) for 4 hours using a magnetic stirrer until the chitosan was completely dissolved to form a uniform transparent solution, and the pH value of the chitosan solution was adjusted to 5.5 using a NaOH solution; (2) Weigh 10 g of sodium alginate, add it to 400 mL of deionized water, and stir it at room temperature for 1 hour until it is completely dissolved to form a uniform viscous solution. Weigh 10 g of modified graphene, add it to 250 mL of deionized water, and use an ultrasonic disperser to ultrasonicate for 30 minutes to obtain a stable polymer hybrid suspension; (3) mixing the chitosan solution, the sodium alginate solution and the polymer hybrid suspension in a volume ratio of 1:1:0.5; (4) Add 30 mL of plasticizer, 20 g of barrier material, 1 g of antimicrobial agent, 2 g of intelligent degradation regulator, 5 g of slow degradation agent, 0.5 g of photosensitizer, 0.2 g of methylene blue, 10 ml of anthocyanin and 0.2 g of bromocresol green and continue stirring at room temperature for 2 hours to ensure that all ingredients are evenly dispersed; (5) Place the mixed solution in a vacuum desiccator and treat it under negative pressure for 30 minutes to remove bubbles in the solution; (6) Slowly pour the degassed solution into the applicator, apply the solution on a clean, flat Teflon plate at a constant speed, and adjust the applicator to control the film thickness to 0.25 mm; (7) The coated film was placed at room temperature for 2 hours to allow the solvent to partially evaporate. The film was then transferred to a drying oven and dried at 50°C and 50% relative humidity for 12 hours. After drying, the film was taken out and equilibrated at room temperature and 65% relative humidity for 24 hours. The film was peeled off from the mold and then immersed in a 2 mmol / L polyvinyl alcohol ester solution for 30 minutes. After treatment, the film was repeatedly washed with deionized water to remove the unreacted polyvinyl alcohol ester solution. The treated film was dried in a drying oven at 40°C for 6 hours. Example

[0029] See also Figure 1 , a high barrier biodegradable food packaging film, the intelligent degradation regulator includes a slow degradation agent and an acid-base regulator; The slow degradation agent uses polylactic acid enzyme and photosensitizer, and the photosensitizer uses benzophenone compounds, transition metal compounds and new degradable near-infrared photosensitizer; The benzophenone compounds have a ketone group in their molecular structure and can be easily excited by light. The benzophenone compounds are selected from acetophenone, hexachloroacetone, tetramethyl-4,4-diaminoketone, tetrabutyl thiophenone disulfide, and diphenylamine. The transition metal compound is selected from transition metal salts of N,N-dialkyldithiocarbamic acid, transition metal salts of salicylic acid, anatase titanium dioxide, calcium oxide, nickel dialkyldithiocarbamate and zinc, Zn, Mn, Ni, Co metal ion complexes, cerium carboxylate, cerium laurate and cerium stearate; The acid-base regulator uses 0.1-0.7 parts of citric acid, 0.2-0.4 parts of nano magnesium hydroxide and 0.1-0.3 parts of trisodium phosphate Take the following raw material components and weight parts: 20g chitosan, 20g sodium alginate, 30mL plasticizer, 1g antibacterial agent, 2g intelligent degradation regulator, 5g slow degradation agent, 0.5g photosensitizer; Further, (1) 20 g of chitosan was weighed and added to 500 mL of 1% acetic acid solution, and stirred at room temperature (25°C) for 4 hours using a magnetic stirrer until the chitosan was completely dissolved to form a uniform transparent solution, and the pH value of the chitosan solution was adjusted to 5.5 using a NaOH solution; (2) Weigh 20 g of sodium alginate, add it to 400 mL of deionized water, and stir it at room temperature for 1 hour until it is completely dissolved to form a uniform viscous solution. Weigh 10 g of modified graphene, add it to 250 mL of deionized water, and use an ultrasonic disperser to ultrasonicate for 30 minutes to obtain a stable polymer hybrid suspension; (3) mixing the chitosan solution, the sodium alginate solution and the polymer hybrid suspension in a volume ratio of 1:1:0.5; (4) Add 30 mL of plasticizer, 1 g of antibacterial agent, 2 g of intelligent degradation regulator, 5 g of slow degradation agent, and 0.5 g of photosensitizer and continue stirring at room temperature for 2 hours to ensure that all ingredients are evenly dispersed; (5) Place the mixed solution in a vacuum desiccator and treat it under negative pressure for 30 minutes to remove bubbles in the solution; (6) Slowly pour the degassed solution into the applicator, apply the solution on a clean, flat Teflon plate at a constant speed, and adjust the applicator to control the film thickness to 0.25 mm; (7) Place the coated film at room temperature for 2 hours to allow the solvent to partially evaporate, then transfer the film to a drying oven and dry it at 50°C and 50% relative humidity for 12 hours. After drying, take out the film and equilibrate it at room temperature and 65% relative humidity for 24 hours.

[0030] The high barrier biodegradable food packaging film prepared in Examples 2-5 was cut into square samples (5×5 cm) and subjected to performance tests, wherein Example 5 was set as the control group.

[0031] Water vapor transmission rate test: GB 1037-1988 "Test method for water vapor permeability of plastic film and sheet - cup method" calculates the water vapor transmission rate of the sample by accurately weighing the weight change of the moisture permeable cup clamped with the sample before and after the sample reaches water vapor transmission equilibrium under the environment of 25℃ and relative humidity of 85%; Oxygen permeability test: GB / T 1038-2000 "Plastic film and sheeting gas permeability test method pressure difference method" uses the sample to separate the permeation cavity into two independent spaces, forming a certain gas pressure difference on both sides of the sample, testing oxygen permeation through the film into the low-pressure side and causing the pressure change on the low-pressure side, thereby calculating the oxygen permeability; Plastic and composite material tensile property test: ISO 527 clamps the sample on the fixture of the tensile testing machine, starts the tensile testing machine, applies tensile force at a constant speed until the sample breaks, and calculates the tensile strength based on the maximum tensile force Fm reached at the beginning of the test and the cross-sectional area of ​​the sample; Antimicrobial test for plastics and other non-porous surfaces: ISO 22196 colony count method, the membrane solution is dissolved in the eluent to prepare a bacterial suspension, and the number of viable bacteria is determined by the plate count method after appropriate dilution. The bactericidal efficiency is calculated by comparing it with the control group.

[0032] The test results are shown in Table 1 Example 5 (Control Group) Example 2 Example 3 Example 4 Water vapor transmission rate g / h·m2 8 0.005 1.1 2.6 Oxygen transmission rate Mol / (m2·s) 12 0.5 1.8 5 Tensile strength N / mm² 8.2 91 10 15.7 Number of live bacteria (pcs) 506 9 142 355 Working principle: chitosan solution, sodium alginate solution and polymer hybrid suspension were mixed in a volume ratio of 1:1:0.5, 30mL plasticizer, 20g barrier material, 1g antimicrobial agent, 2g smart degradation regulator, 5g slow degradation agent, 0.5g photosensitizer, 0.2g methylene blue, 10ml anthocyanin and 0.2g bromocresol green were added and stirred for 2 hours at room temperature to ensure that all ingredients were evenly dispersed; The mixed solution was placed in a vacuum dryer and treated under negative pressure for 30 minutes to remove bubbles in the solution. The degassed solution was slowly poured into a coater and coated on a clean, flat Teflon plate at a constant speed. The coater was adjusted to control the film thickness to 0.25 mm. The coated film was placed at room temperature and allowed to stand for 2 hours to allow the solvent to partially evaporate. The film was transferred to a drying oven and dried for 12 hours at a temperature of 50°C and a relative humidity of 50%. After drying, the film was taken out and balanced in an environment of room temperature and a relative humidity of 65% for 24 hours. The film was peeled off from the mold, and then the film was immersed in a 2 mmol / L polyvinyl alcohol ester solution for 30 minutes. After treatment, the film was repeatedly washed with deionized water to remove unreacted polyvinyl alcohol ester solution. The treated film was dried in a drying oven at a temperature of 40°C for 6 hours.

[0033] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high barrier biodegradable food packaging film, Features: It includes the following main components and weight parts: 4-25 parts of polymer hybrid, 6-15 parts of enzymatic degradation enhancer, 10-25 parts of barrier material, 55-80 parts of bio-based polymer, 30-40 parts of intelligent degradation regulator, intelligent responsive material, 10-15 parts of novel starch derivative, 13-27 parts of novel polybioester, 20-40 parts of chitosan-sodium alginate complex; The polymer hybrid is modified graphene, the enzymatic degradation enhancer is cellulase, amylase, metal ions and coenzymes, the barrier material is polyvinyl alcohol ester, polyvinyl alcohol ether, polycaprolactone, microalgae film and polymer nanofiber, and the bio-based polymer is plant fiber and polyhydroxybutyrate; The food packaging film has a nano-interlayer structure.

2. A high barrier biodegradable food packaging film according to claim 1, Features: The smart responsive material is 0.5-2 parts of self-assembled microcapsules, the responsive monomer is N-isopropylacrylamide, the microcapsule shell is polylactic acid-polyethylene glycol copolymer, and the crosslinking agent is mercaptopropionic acid; The humidity-responsive polymer is polyvinyl alcohol, the photosensitive polymer is styrene, and the photocrosslinking agent is dinitrophenol; The acid-base responsive polymer is a polyacrylic acid compound, and the polyacrylic acid compound is sodium polyacrylic acid and acrylic acid-hydroxyethyl methacrylate copolymer.

3. The high barrier biodegradable food packaging film according to claim 1, Features: The intelligent degradation regulator includes a slow degradation agent and an acid-base regulator; The slow degradation agent uses polylactic acid enzyme and photosensitizer, and the photosensitizer uses benzophenone compounds, transition metal compounds and new degradable near-infrared photosensitizer; The benzophenone compounds have a ketone group in their molecular structure and can be easily excited by light. The benzophenone compounds are selected from acetophenone, hexachloroacetone, tetramethyl-4,4-diaminoketone, tetrabutyl thiophenone disulfide, and diphenylamine. The transition metal compound is selected from transition metal salts of N,N-dialkyldithiocarbamic acid, transition metal salts of salicylic acid, anatase titanium dioxide, calcium oxide, nickel dialkyldithiocarbamate and zinc, Zn, Mn, Ni, Co metal ion complexes, cerium carboxylate, cerium laurate and cerium stearate; The acid-base regulator uses 0.1-0.7 parts of citric acid, 0.2-0.4 parts of nano magnesium hydroxide and 0.1-0.3 parts of trisodium phosphate.

4. A high barrier biodegradable food packaging film according to claim 3, Features: The novel degradable near-infrared photosensitizer is a porphyrin compound and its derivatives. The porphyrin compound and its derivatives are degraded while generating active oxygen under light. When the light ends, the photosensitizer is completely converted into a low-toxic substance without photoactivity.

5. The high barrier biodegradable food packaging film according to claim 1, Features: The food packaging film also includes the following components and weight parts: 0.5-2 parts of toughening agent, 1-3 parts of nanofiber reinforcing agent, 0.3-0.6 parts of moisture control agent, antibacterial agent, 2-7 parts of polymer sealant, 0.6-1.8 parts of coating modifier, 0.5-0.9 parts of enzymolysis agent, 1-5 parts of microbial degradation agent, 1-9 parts of matting agent; The toughening agent is a bio-based toughening agent, which is a mixture of starch polymer and succinic acid; The humidity control agent adopts modified silica gel and bamboo charcoal; The antimicrobial agent used was 0.3 parts of glucomannan, 9 parts of aloe-emodin, and 15 parts of mannose-6-phosphate; The polymer sealant uses polyurethane; The coating modifiers are water-based polyurethane and water-based acrylic; The microbial degradation agent uses a composite microbial agent, Pseudomonas, Candida and Rhodotorula; The matting agent is a polyacrylate resin with an epoxy group, with a softening point between 120-130°C and a viscosity between 400-600cps.

6. The high barrier biodegradable food packaging film according to claim 1, Features: The polyhydroxybutyrate has a melting point of 175° C. and is produced by a microbial fermentation agent.

7. The high barrier biodegradable food packaging film according to claim 1, Features: The polycaprolactone is prepared by ring-opening polymerization of ε-caprolactone under the conditions of metal organic compound tetraphenyltin as catalyst and dihydroxy / trihydroxy as initiator, with a melting point of 60-63° C. and a density of 1.021 g / cm³.

8. The high barrier biodegradable food packaging film according to claim 5, Features: The starch polymer and succinic acid mixture is formed by combining starch polymer and succinic acid / succinic acid derivatives through esterification reaction, with starch polymer as the main chain and succinic acid / succinic acid derivatives as the side chain, which are connected together through ester bonds.

9. A method for preparing a high barrier biodegradable food packaging film, applicable to the high barrier biodegradable food packaging film according to any one of claims 1 to 8, Features: The preparation method comprises the following steps: (1) Weigh 20 g of chitosan and add it to 500 mL of 1% acetic acid solution. Use a magnetic stirrer to stir at room temperature for 4 hours until the chitosan is completely dissolved to form a uniform transparent solution. Use NaOH solution to adjust the pH value of the chitosan solution to 5.5-6.0; (2) Weigh 20 g of sodium alginate and add it to 400 mL of deionized water. Stir at room temperature for 1 hour until it is completely dissolved to form a uniform viscous solution. (3) mixing the chitosan solution, the sodium alginate solution and the polymer hybrid suspension in a volume ratio of 1:1:0.5; (4) Add 30 mL of plasticizer, 20 g of barrier material, 1 g of antimicrobial agent, 2 g of intelligent degradation regulator, 0.5 g of photosensitizer, 0.2 g of methylene blue, 10 ml of anthocyanin and 0.2 g of bromocresol green and continue stirring at room temperature for 2 hours to ensure that all ingredients are evenly dispersed; (5) Place the mixed solution in a vacuum desiccator and treat it under negative pressure for 30 minutes to remove bubbles in the solution; (6) Slowly pour the degassed solution into the applicator, apply the solution on a clean, flat film forming mold at a constant speed, and adjust the applicator to control the thickness of the film; (7) The coated film was placed at room temperature for 2 hours to allow the solvent to partially evaporate. The film was then transferred to a drying oven and dried at 50°C and 50% relative humidity for 12 hours. After drying, the film was taken out and equilibrated at room temperature and 65% relative humidity for 24 hours. The film was peeled off from the mold and then immersed in a 2 mmol / L polyvinyl alcohol ester solution for 30 minutes. After treatment, the film was repeatedly washed with deionized water to remove the unreacted polyvinyl alcohol ester solution. The treated film was dried in a drying oven at 40°C for 6 hours.

10. The method for preparing a high barrier biodegradable food packaging film according to claim 9, Features: The preparation method further comprises the following steps: (8) Preparation of polyhydroxybutylate Select Pseudomonas acidophilus / recombinant Escherichia coli, prepare fermentation medium, inoculate and ferment at about 37°C for 48-72 hours, collect bacteria and break cell walls, extract products with organic solvent chloroform, precipitate, filter and dry to obtain pure polyhydroxybutyrate; (9) Starch polymer and succinic acid mixture Disperse starch in water, adjust the pH to 8-9, slowly add octenyl succinic anhydride, control the temperature at 25-40°C, and react for 2-4 hours to graft the octenyl succinic acid groups onto the starch molecules; Add aluminum hydroxide solution to the esterified starch, stir evenly, and react for 0.5-2 hours to allow aluminum ions to combine with the esterified starch; The pH of the reaction solution is adjusted to 6-7 with hydrochloric acid / sodium hydroxide, the product is separated by centrifugation, and washed with water to remove unreacted raw materials and by-products; The wet product is dried at 50-60°C to constant weight, and the dried product is crushed and sieved to obtain fine powdered aluminum starch octenylsuccinate.

Citation Information

Cited By

  • Barrier coating composition for paper-based material, barrier coating and paper-based material

    CN119434019A

  • Barrier coating composition for paper-based material, barrier coating and paper substrate

    CN119434019B

  • Fluoride-free antibacterial TPU protective film and preparation method thereof

    CN119505520A

  • High-barrier flexible optical conductive film and preparation method thereof

    CN121812249A